Addressing the Perfect Storm: Biomarkers in Obesity and Pathophysiology of Cardiometabolic Risk - Aleksandrova, Krasimira; Mozaffarian, Dariush; Pischon, Tobias (Clinical chemistry (Baltimore, Md.), 2018)
The worldwide rise of obesity has provoked intensified research to better understand its pathophysiology as a means for disease prevention. Several biomarkers that may reflect various pathophysiological pathways that link obesity and cardiometabolic diseases have been identified over the past decades. We summarize research evidence regarding the role of established and novel obesity-related biomarkers, focusing on recent epidemiological evidence for detrimental associations with cardiometabolic diseases including obesity-related cancer. The reviewed biomarkers include biomarkers of glucose-insulin homeostasis (insulin, insulin-like growth factors, and C-peptide), adipose tissue biomarkers (adiponectin, omentin, apelin, leptin, resistin, and fatty-acid-binding protein-4), inflammatory biomarkers (C-reactive protein, interleukin 6, tumor necrosis factor α), and omics-based biomarkers (metabolites and microRNAs). Although the evidence for many classical obesity biomarkers, including adiponectin and C-reactive protein (CRP), in disease etiology has been initially promising, the evidence for a causal role in humans remains limited. Further, there has been little demonstrated ability to improve disease prediction beyond classical risk factors. In the era of "precision medicine," there is an increasing interest in novel biomarkers, and the extended list of potentially promising biomarkers, such as adipokines, cytokines, metabolites, and microRNAs, implicated in obesity may bring new promise for improved, personalized prevention. To further evaluate the role of obesity-related biomarkers as etiological and early-disease-prediction targets, well-designed studies are needed to evaluate temporal associations, replicate findings, and test clinical utility of novel biomarkers. In particular, studies to determine the therapeutic implications of novel biomarkers beyond established metabolic risk factors are highly warranted.